2014
DOI: 10.5114/hpr.2015.47088
|View full text |Cite
|
Sign up to set email alerts
|

Pain-related and performance anxiety and their contribution to pain in music students: a pilot study

Abstract: Pain complaints are common among musicians, whose occupation is highly demanding on both a physical and a psychological level. The purpose of the present study was to better understand the severity of musculoskeletal pain in orchestra musicians by measuring the potential contributions of biological (medical diagnosis), psychosocial (age, gender, instrument, practice and exercising history, and occupational satisfaction), and psychological (pain-related anxiety, performance anxiety, and affect) variables. parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
(46 reference statements)
2
11
0
1
Order By: Relevance
“…This classification refers to the target population that was not necessarily the same as those from whom data were collected (e.g., Rickert et al [61][62][63]151], Ackermann and Driscoll [175], Ajidahun and Phillips [186], and McKechnie and Jacobs [177]). , and university orchestral students with those who had not played any music for at least the past year [116]. Kok et al [54,55] also compared the medical students who did and did not play a musical instrument.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…This classification refers to the target population that was not necessarily the same as those from whom data were collected (e.g., Rickert et al [61][62][63]151], Ackermann and Driscoll [175], Ajidahun and Phillips [186], and McKechnie and Jacobs [177]). , and university orchestral students with those who had not played any music for at least the past year [116]. Kok et al [54,55] also compared the medical students who did and did not play a musical instrument.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Despite the large number of prevalence studies identified, few statistically compared the MSS prevalence of musicians with other populations [28, [53][54][55]70,75,116,123,161,171]. Such comparisons are required to contextualize the findings of prevalence studies.…”
Section: Ijomeh 2019;32(3)mentioning
confidence: 99%
See 1 more Smart Citation
“…The specific musical tasks reported were: playing27,28,29, 38, 39, 43, 45, 46, 49, 50, 57, 60, 75, 79, 80, 91,92,93, 116, 118, 120, 121, 125, 128, 135, 136, 138, 142,143,144,145, 147, 149,150,151,152,153, 155, 157, 159 ) , performance30, 31, 34,35,36,37, 77, 127, 133, 140,141,142, 146, 148, 154, 156, 158, 160 ) , practice/performance133 ) , marching140 ) , drum-corp140 ) , instrument135 ) , flute148, 150 ) , trombone89 ) , piano166 ) , and ‘voice usage’161 ) . Two studies used the term ‘music-related’113, 139 ) .…”
Section: Resultsmentioning
confidence: 99%
“…pain or injuries, appear to have been used interchangeably in 25 articles (21 studies)34,35,36,37,38,39, 43, 50, 57, 60, 75, 80, 89, 118, 121, 124, 136, 138, 140, 142, 146, 150, 151, 161, 166 ) . How musical activity and MSS were related was not clear in 31 studies34, 38, 39, 43, 46, 50, 57, 60, 75, 77, 89, 91, 92, 113, 120, 121, 125, 139,140,141,142, 145,146,147,148,149,150,151, 157,158,159, 162 ) . A total of 17 studies defined ‘music-related’ MSS as MSS that interfered with musical activity27,28,29,30,31, 35,36,37, 45, 46, 79, 93, 116, 118, 124, 128, 135, 136, 138, 143, 153, 154, 156, 160 ) (all bar one,143 ) using Zaza et al.…”
Section: Resultsmentioning
confidence: 99%